2013
DOI: 10.1002/per.1891
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Self–Control: A Brief Measure of Persistent Goal Pursuit

Abstract: Habitual self‐control is defined as a trait‐like personal resource factor that facilitates the enactment of difficult intentions. A 14‐item Habitual Self‐Control Questionnaire (HSCQ) was developed to assess this trait. Reliability, factorial validity, and criterion validity were assessed in five undergraduate student subsamples with an overall N of 2224. Internal consistency was .81 across the entire sample, and test–retest reliability was .83 over a one‐month interval. The HSCQ showed a theoretically meaningf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…A recent online study conducted with 923 adults in the UK showed that higher eating self-regulatory skills were related to higher fruit and vegetables intake and to lower unhealthy snack intake and sugary drinks intake, as well as lower BMI ( Kliemann, Beeken, Wardle, & Johnson, 2016 ). Similar results were found in studies conducted specifically with undergraduate students ( Price, Higgs, & Lee, 2017 ; Schroder, Ollis, & Davies, 2013 ; Tomasone, Meikle, & Bray, 2015 ). However, the majority of these studies had cross-sectional designs, which cannot indicate causality.…”
Section: Introductionsupporting
confidence: 87%
“…A recent online study conducted with 923 adults in the UK showed that higher eating self-regulatory skills were related to higher fruit and vegetables intake and to lower unhealthy snack intake and sugary drinks intake, as well as lower BMI ( Kliemann, Beeken, Wardle, & Johnson, 2016 ). Similar results were found in studies conducted specifically with undergraduate students ( Price, Higgs, & Lee, 2017 ; Schroder, Ollis, & Davies, 2013 ; Tomasone, Meikle, & Bray, 2015 ). However, the majority of these studies had cross-sectional designs, which cannot indicate causality.…”
Section: Introductionsupporting
confidence: 87%
“…Participants completed three items adapted from Schroder, Ollis, and Davies’ (2013) assessment of goal accomplishment: (a) “To what degree have you met your intentions to practice meditation?” (0% to 100%); (b) “How successful have you been at following your intentions to practice meditation?” (1 = very unsuccessful to 7 = very successful ); and (c) “As of today, how satisfied are you with the degree to which you have met your intentions to practice meditation?” (1 = very dissatisfied to 7 = very satisfied ). We created a composite score calculated as the mean of standardized scores for each item, with higher scores indicating greater goal accomplishment (α = .91).…”
Section: Methodsmentioning
confidence: 99%
“…It is composed of a series of 40 pairs of dichotomous statements from which one must be selected. Goal-Oriented Personality Traits: The Habitual Self-Control Questionnaire (HSCQ, Schroder, Ollis, & Davies, 2013 ) is a 14-item instrument measuring variations in people's commitment to completing tasks and their self-perceptions around their drive for goal-pursuit. Participants express their level of agreement to each item on a 5-point Likert scale, ranging from disagree strongly (1) to agree strongly (5).…”
Section: Methodsmentioning
confidence: 99%